Impacts of the western hemisphere free trade area on the international trade of soybean oil, soybean meal and soybeans - Jaafar, Abdul Hamid (Universiti Utara Malaysia, 2004)
A major multi-county free trade agreement currently under negotiation is the Free Trade Area of the Americas (FTAA). The agreement is proposed to be operational by January 2005 and will encompass 34 countries in the Western Hemisphere. Soybeans and soybean products are important export commodities in the Western Hemisphere. It is expected that tariffs and duties on these commodities will be intensely negotiated. The purpose of this paper is to analyze effects of the FTAA implementation on international trade of soybean oil, soybean meal and soybeans. Emphases of investigations are on how the implementation of FTAA is afected by Brazil's soybean output expansion and China's accession into the World Trade Organization. The method of analysis is via the spatial equilibrium model that includes all countries in the Western Hemisphere and several regions outside the hemisphere. Four alternative trade scenarios were simulated and their results were compared with those from the baseline model. All scenarios indicated that the U.S. and Brazil would be able to at least expand their exports of soybean oil or soybean meal.